2008
DOI: 10.5194/angeo-26-3783-2008
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous observations of Polar Mesosphere Summer Echoes at two different latitudes in Antarctica

Abstract: Abstract. Simultaneous observations of Polar MesosphereSummer Echoes (PMSE) at Wasa and Davis in Antarctica have been compared. Data with simultaneous observations were obtained for 16 days between 18 January and 5 February 2007. Wasa is at a higher geographic latitude than Davis, but at lower geomagnetic latitude. PMSE strength and occurrence frequency were significantly higher at Wasa. The variation of daily PMSE occurrence over the measurement period was in agreement with temperature and frost-point estimat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 23 publications
2
6
0
Order By: Relevance
“…This seemed to be consistent with the (limited) information then available, suggesting that summer mesopause temperatures at about 70 • latitude were about the same in both hemispheres (Lübken et al, 1999). Nilsson et al (2008) compared PMSE between Wasa and Davis, Antarctica (69 • S, 78 • E), and found about half the occurrence rates at Davis compared to Wasa, which was consistent with satellite indications of temperature differences at the time of those measurements between 69 • S and 73 • S. Latteck et al (2008) , and found occurrence rates of 18 %, 83 % and 38 %, respectively, with mean and maximum reflectivities also varying in the same order. For the same time interval, and the same detection threshold, Smirnova et al (2010) found about a 75 % occurrence rate at Kiruna, which gives a consistent difference between Andenes/Kiruna/Wasa (all about the same) and Davis.…”
supporting
confidence: 70%
“…This seemed to be consistent with the (limited) information then available, suggesting that summer mesopause temperatures at about 70 • latitude were about the same in both hemispheres (Lübken et al, 1999). Nilsson et al (2008) compared PMSE between Wasa and Davis, Antarctica (69 • S, 78 • E), and found about half the occurrence rates at Davis compared to Wasa, which was consistent with satellite indications of temperature differences at the time of those measurements between 69 • S and 73 • S. Latteck et al (2008) , and found occurrence rates of 18 %, 83 % and 38 %, respectively, with mean and maximum reflectivities also varying in the same order. For the same time interval, and the same detection threshold, Smirnova et al (2010) found about a 75 % occurrence rate at Kiruna, which gives a consistent difference between Andenes/Kiruna/Wasa (all about the same) and Davis.…”
supporting
confidence: 70%
“…In particular, when considering effects from different contributors to PMSE variability, it is important to separate strong ionization effects due to energetic particle precipitation from others players. In particular, PMSE and NLC have different daily variations: the former are observed to be strongest around noon and weakest in the evening hours, whereas the latter have a maximum in the morning hours and a minimum around noon (Nilsson et al, 2008;Smirnova et al, 2010;Fiedler et al, 2005). Thus, it is likely that PMSE have a strong variation component due to a highly variable ionization constituent.…”
Section: Introductionmentioning
confidence: 99%
“…PMSE have a distinctly different daily variation from noctilucent clouds, being strongest around noon and weakest in the evening, in both hemispheres (e.g. Nilsson et al, 2008;Smirnova et al, 2010). If PMSE are caused by the same (or similar, but smaller) ice particles as noctilucent clouds we might expect a better correlation.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, for averages over the whole season, during any particular hour of LT, median volume reflectivities are lower than means by about a factor 20. Previous estimates of the daily variation of PMSE reflectivity at Wasa/Aboa published in Nilsson et al (2008) are mean values, and are therofore much higher in numerical value. The diurnal variation in the present data, which represents 2 months of observations during the main PMSE season, is also slightly different from that found in Nilsson et al (2008), which represented only 16 days of observations, at the end of the previous season.…”
Section: Diurnal Variation Ice Mass Density Derived From Pmsementioning
confidence: 99%
See 1 more Smart Citation